P (x)= 2x cube -7x square +9x -13, g (x)= x-3
please solve this solution immediately...
Attachments:
![](https://hi-static.z-dn.net/files/d42/7ab491b41cfe120f390b0d17cc9f345c.jpg)
Answers
Answered by
49
hello here is your answer by Sujeet yaduvanshi ✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌✌
Given that:)
P(x)=2x³-7x²+9x-13
g(x)=x-3
x-3=0
x=3
then,
2x³-7x²+9x-13
2.(3)³-7(3)²+9(3)-13
2.27-7.9+27-13
54-63+27-13
54+27-63-13
81-76
5
that's all
that's all
by Sujeet
Given that:)
P(x)=2x³-7x²+9x-13
g(x)=x-3
x-3=0
x=3
then,
2x³-7x²+9x-13
2.(3)³-7(3)²+9(3)-13
2.27-7.9+27-13
54-63+27-13
54+27-63-13
81-76
5
that's all
that's all
by Sujeet
Answered by
8
Answer:
thanks best of luck
Attachments:
![](https://hi-static.z-dn.net/files/d55/86156c6be50a055df0f9766d75cd6e7a.jpg)
Similar questions